Primary Immune Responses and Affinity Maturation Are Controlled by IgD - Amendt, Timm; Ayoubi, Omar El; Linder, Alexandra T.; Allies, Gabriele; Young, Marc; Setz, Corinna S.; Jumaa, Hassan (Frontiers in Immunology, 2021)
Mature B cells co-express IgM and IgD B cell antigen receptors (BCR) on their surface. While IgM BCR expression is already essential at early stages of development. The role of the IgD-class BCR remains unclear as most B cell functions appeared unchanged in IgD-deficient mice. Here, we show that IgD-deficient mice have an accelerated rate of B cell responsiveness as they activate antibody production within 24h after immunization, whereas wildtype (WT) animals required 3 days to activate primary antibody responses. Strikingly, soluble monovalent antigen suppresses IgG antibody production induced by multivalent antigen in WT mice. In contrast, IgD-deficient mice were not able to modulate IgG responses suggesting that IgD BCR controls the activation rate of B cells and subsequent antibody production by sensing and distinguishing antigen-valences. Using an insulin-derived peptide we tested the role of IgD in autoimmunity. We show that primary autoreactive antibody responses are generated in WT and in IgD-deficient mice. However, insulin-specific autoantibodies were detected earlier and caused more severe symptoms of autoimmune diabetes in IgD-deficient mice as compared to WT mice. The rapid control of autoimmune diabetes in WT animals was associated with the generation of high-affinity IgM that protects insulin from autoimmune degradation. In IgD-deficient mice, however, the generation of high affinity protective IgM is delayed resulting in prolonged autoimmune diabetes. Our data suggest that IgD is required for the transition from primary, highly autoreactive, to secondary antigen-specific antibody responses generated by affinity maturation.